2022
DOI: 10.1038/s41598-022-19600-y
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous speciation of chromate, molybdate and arsenate in lysimetric water from geotechnical composites installed in field lysimeters

Abstract: Anion-exchange high performance liquid chromatography inductively coupled plasma mass spectrometry (HPLC-ICP-MS) was used for simultaneous speciation of chromate, molybdate and arsenate. The repeatability of measurement tested for multielemental standard solution of chromate, molybdate and arsenate (50 ng mL−1 of Cr, Mo and As, pH 12) was ± 0.9%, ± 4.9% and ± 4.1%, respectively. Limits of quantification (LOQs) were low (0.53 ng mL−1 for chromate and arsenate and 1.03 ng mL−1 for molybdate, expressed as element… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 32 publications
(24 reference statements)
0
7
0
Order By: Relevance
“…The majority of Cr speciation procedures described in the past year have featured HPLC-ICP-MS . The group of Milacic and Scancar has reported on speciation in wine and beer, 65 speciation and bioimaging in dandelions, 66 the simultaneous speciation of arsenate, chromate, and molybdate in lysimeter water, 67 and the reduction of Cr VI by bacteria in tannery effluent. 68 In each of these studies, Cr speciation was carried out by an HPLC-ICP-MS procedure, originally described in 2012, in which analytes were separated on a SAX fast-protein column (Mono Q HR 5/5) that had been conditioned with 1.0 mol L −1 NaCl.…”
Section: Elemental Speciation Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of Cr speciation procedures described in the past year have featured HPLC-ICP-MS . The group of Milacic and Scancar has reported on speciation in wine and beer, 65 speciation and bioimaging in dandelions, 66 the simultaneous speciation of arsenate, chromate, and molybdate in lysimeter water, 67 and the reduction of Cr VI by bacteria in tannery effluent. 68 In each of these studies, Cr speciation was carried out by an HPLC-ICP-MS procedure, originally described in 2012, in which analytes were separated on a SAX fast-protein column (Mono Q HR 5/5) that had been conditioned with 1.0 mol L −1 NaCl.…”
Section: Elemental Speciation Analysismentioning
confidence: 99%
“…Additionally, spatially resolved studies of leaves with LA-ICP-MS showed that Cr was localised mainly at the apices, indicating that Cr species were relatively mobile during the transport within the leaf. For speciation of As, Cr and Mo in lysimeter waters, 67 in support of a study of the leaching of these elements from 3 geotechnical composites made of recycled waste in both compacted and uncompacted (20 times less dense) forms, the same HPLC column was used, though this time the eluent was a gradient from 0 to 0.7 mol L −1 over 10 min at a flow rate of 1.5 mL min −1 . The samples were adjusted to pH 12 and 100 μL was injected.…”
Section: Elemental Speciation Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…6 , and AsO 4 3− in 0.2% NaOH and 0.3% Na 2 CO 3 buffer (pH 12). 7 Although the methods described above are accurate enough, they are usually limited to operation in the laboratory. The process of sample collection and transportation might change the temperature and environment, which may lead to changes in the forms of HMIs, affecting the reliability of actual detection.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Drinčić et al carried out the simultaneous speciation analysis of CrO 4 2– , AsO 4 3– , MoO 4 2– , and VO 4 3– in alkaline samples by high-performance liquid chromatography inductively coupled plasma mass spectrometry (HPLC–ICP-MS) with the obtained limits of detection as 0.2, 0.4, 1, and 2 ng mL –1 , respectively . Djurić et al used anion-exchange HPLC–ICP-MS to analyze CrO 4 2– , MoO 4 2– , and AsO 4 3– in 0.2% NaOH and 0.3% Na 2 CO 3 buffer (pH 12) . Although the methods described above are accurate enough, they are usually limited to operation in the laboratory.…”
Section: Introductionmentioning
confidence: 99%